The Effectiveness of Dialogical Patrol of the Turjawali Unit of the Samapta Unit in Preventing the Crime of Theft with Weights in the Jurisdiction of the Malang Police - Mufadhol, Annaqib (Advances in Police Science Research Journal, 2024)
Based on Law Number 2 of 2002 concerning the State Police of the Republic of Indonesia, paragraph 5 concerning the State Police of the Republic of Indonesia, it explains that dynamic conditions in society are conditions for the implementation of the national development process starting from guaranteed security, order and upholding the law as well as achieving truth that contains capabilities. to develop community strength in maintaining and preventing all forms of law violations and also other forms of law violations that create public inconvenience is the meaning of public security and order based on article 1 paragraph 5 of Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia. The operational function of the National Police in creating security and social order is the task of the Samapta function which is under Baharkam Polri. Samapta Bhayangkara or often called Samapta, which means that the police at any time, anywhere must always be ready to create conducive security and social order so that there are no security disturbances. Samapta is the operational function of the police which is given the task and authority to prevent the threshold of preventive disturbances. In the Regulation of the Head of the Security Maintenance Agency for the Police of the Republic of Indonesia for Implementing Patrols, there are several strategies, including dialogical patrols. Dialogical patrols are activities carried out by members of the National Police who carry out dialogue with the community with the aim of conveying public security and order messages related to currently prominent issues.